ChemInform Abstract: Novel Co3O4 Porous Polyhedrons Derived from Metal—Organic Framework Toward High Performance for Electrochemical Energy Devices. Issue 31 (14th July 2016) - Chen, Youcun; Hu, Lin
Abstract: The title material is prepared by annealing Co3 [Co(CN)6 ]2 at 400 °C in air for 1 h.